2022
DOI: 10.1093/ibd/izab348
|View full text |Cite
|
Sign up to set email alerts
|

Natural Herbal Remedy Wumei Decoction Ameliorates Intestinal Mucosal Inflammation by Inhibiting Th1/Th17 Cell Differentiation and Maintaining Microbial Homeostasis

Abstract: Background Evidence has shown that the traditional Chinese herbal medicine Wumei decoction (WMD) has a protective effect on ulcerative colitis. Here, we studied the anti-inflammatory effects and potential mechanisms of WMD on chronic colitis in mice. Methods A dextran sulfate sodium (DSS)–induced chronic colitis model and CD45RBhighCD4+ T cell transfer model were established in mice. Body weight, Disease Activity Index, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Ileibacterium is a gram-positive anaerobic bacterium related to metabolic health that can decompose polysaccharides ( Wang et al, 2021 ). An increased relative abundance of Ileibacterium has been observed in animal models of intestinal microecological disorders ( Xiao et al, 2021 ; Wu et al, 2022 ). Akkermansia was higher in the SGA group on days 5 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…Ileibacterium is a gram-positive anaerobic bacterium related to metabolic health that can decompose polysaccharides ( Wang et al, 2021 ). An increased relative abundance of Ileibacterium has been observed in animal models of intestinal microecological disorders ( Xiao et al, 2021 ; Wu et al, 2022 ). Akkermansia was higher in the SGA group on days 5 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the expression of Deoxycytidine, N-Acetyl-D-Galactosamine, and Phytosphingosine, all of which have some degree of toxicity and mucosal irritation, was elevated in the CRA model, while the high expression of these metabolites is considered to be closely tied with colorectal cancer (Goedert et al, 2014;Brown et al, 2016;Sun et al, 2021), and all showed a decreasing trend in expression after treatment with SZF. It has been reported that Mume Fructus, a vital component of SZF, has effects of maintaining microbial homeostasis, inhibiting the differentiation of CD4+ T cells in intestinal mucosa and secretion of pro-inflammatory cytokines such as TNFα (tumor necrosis factor α), IL-1β (interleukin 1β), γ-IFN (interferon γ) and IL-17A (Interleukin 17A), so as to improve intestinal mucosal inflammation (Wu et al, 2022). Therefore, SZF may suppress the progression of the adenomacarcinoma sequence by inhibiting the intestinal inflammatory response and modulating the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In the formula, Mume Fructus has the effect of regulating intestinal flora and inhibiting inflammation to protect intestinal mucosa. Hedysarum multijugum Maxim and licorice have effects related to alleviating intestinal flora dysbiosis and improving intestinal barrier dysfunction (Wu et al, 2022). Entada phaseoloides have the effect of inducing apoptosis pathway to inhibit cancer cell growth (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal lamina propria mononuclear cells (LPMCs) were isolated from mouse colon tissues ( Wu et al, 2022 ). For fluorescence-activated cell sorting (FACS) analysis, isolated cells were suspended in FACS buffer, and single-cell suspensions were stained with the following antibodies: APC anti-mouse CD3, FITC anti-mouse CD4, PE anti-mouse CD8, PE/Cy7 anti-mouse B 220, APC anti-mouse CD11b, FITC anti-mouse F4/80, PerCP-cy5.5 anti-mouse Ly6C, PE/Cy7 anti-mouse Ly6G, APC anti-mouse CD11b, PE anti-mouse CD11c, and FITC anti-mouse MHC II.…”
Section: Methodsmentioning
confidence: 99%